Sacred and Rational Negotiations: The Contestation between Ulu Desa and Prajuru Desa in Pedawa and Julah, North Bali - Paramita, Ida Bagus Gede; Suarka, I Nyoman; Pujaastawa, Ida Bagus Gde; Suardiana, I Wayan (International Journal of Multidisciplinary Sciences, 2025)
This study examines the contestation between Ulu Desa (sacred-traditional authority) and Prajuru Desa (administrative authority) in the Bali Aga villages of Pedawa and Julah, which reflects the ongoing tension between customary governance and state regulation. The research aims to analyze how historical trajectories, regulatory frameworks, and socio-economic transformations have shaped the dynamics between sacred and bureaucratic leadership. Using a qualitative descriptive approach, data were collected through in-depth interviews, participant observation, and document analysis, and interpreted with Bourdieu’s concepts of habitus, capital, and field as well as Foucault’s theories on power and discourse. The findings reveal that, (1) historical practices of surveillance embedded dual forms of discipline ritual and administrative within village governance, (2) the penetration of state mechanisms, particularly through village competitions and regional regulations, gradually displaced sacred legitimacy in favor of bureaucratic authority and (3) socio-economic factors such as migration, education, technology, and financial support further reinforced the dominance of Prajuru Desa. Nevertheless, Ulu Desa continues to hold symbolic significance as a guardian of cosmological order. In conclusion, the study demonstrates that the contestation between these two institutions illustrates a hybridization of power in Bali Aga society, where tradition and modernity coexist through tension, negotiation, and adaptation.